DNA repair activation and apoptosis suppression in keratinocytes as a possible mechanism of cytoprotective action of plant polyphenols under conditions of UV-irradiation - Kostyuk, Vladimir A.; Potapovich, Alla I.; Suhan, Tatyana O.; Albuhaydar, Ahmed; Shman, Tatyana V.; Ermilova, Tatyana I.; de Luca, Chiara (Experimental Biology and Biotechnology, 2019)
The work investigated the responses of cultured human keratinocytes to ultraviolet radiation in the C range (UVC) with and without a number of plant polyphenolic compounds. The experimental data obtained in this work indicate a cytoprotective effect of the PPs added immediately after UVC exposure. The cytoprotective activity of plant polyphenolic compounds was reduced in the series: acacetin, silybin, baikalein, leontopodium acid, quercetin, cyanidine chloride, taxifolin, trans-ferulic acid. The effect of UVC irradiation with and without of acacetin on the process of phosphorylation of histones H2AX, the triggering mechanism for the repair of single-stranded DNA damage, was also investigated in keratinocytes. It has been established that, H2AX phosphorylation is activated in response to UVC radiation and acacetin has a significant effect on the kinetics of this process. It is concluded that the PPs can reduce the destructive effect of UVR on the skin cells, activating the process of repairing genetic damage.
Keywords: ultraviolet radiation in the C range; UVR; plant polyphenolic compounds; inflammatory mediators; keratinocytes; histone H2AX